A Systematic Review on Anti-diabetic Properties of Chalcones - Rocha, Sónia; Ribeiro, Daniela; Fernandes, Eduarda; Freitas, Marisa (Current Medicinal Chemistry, 2020)
The use of anti-diabetic drugs has been increasing worldwide and the evolution of therapeutics has been enormous. Still, the currently available anti-diabetic drugs do not present the desired efficacy and are generally associated with serious adverse effects. Thus, entirely new interventions, addressing the underlying etiopathogenesis of type 2 diabetes mellitus, are required. Chalcones, secondary metabolites of terrestrial plants and precursors of the flavonoids biosynthesis, have been used for a long time in traditional medicine due to their wide-range of biological activities, from which the anti-diabetic activity stands out. This review systematizes the information found in literature about the anti-diabetic properties of chalcones, in vitro and in vivo. Chalcones are able to exert these properties by acting in different therapeutic targets: Dipeptidyl Peptidase 4 (DPP-4); Glucose Transporter Type 4 (GLUT4), Sodium Glucose Cotransporter 2 (SGLT2), α-amylase, α-glucosidase, Aldose Reductase (ALR), Protein Tyrosine Phosphatase 1B (PTP1B), Peroxisome Proliferator-activated Receptor-gamma (PPARγ) and Adenosine Monophosphate (AMP)-activated Protein Kinase (AMPK). Chalcones are, undoubtedly, promising anti-diabetic agents, and some crucial structural features have already been established. From the Structure-Activity Relationships analysis, it can generally be stated that the presence of hydroxyl, prenyl and geranyl groups in their skeleton improves their activity for the evaluated anti-diabetic targets.
Keywords: Protein Tyrosine Phosphatase 1B (PTP1B)